The game-players of Titan - Dick, Philip K. (New York : Vintage Books, 1992)
The last inhabitants of planet Earth fall prey to Bluff, a dangerous game of chance that determines the players' futures, and Pete Garden's next match is against a non-human opponent with stakes so high they could change the future for everyone.
Adult.
Adult
Keywords: Games -- Fiction; Games -- Fiction; Science fiction; Science fiction